School Environment and Academic Persistence of Newcomer Students: The Roles of Teachers and Peers - Reza Nakhaie; Howard Ramos; Fatima Fakih (Journal of Teaching and Learning, 2022)
This paper explores the relationship between the social context of schools, measured in terms of perceptions of teacher support and students’ openness to diversity, and the academic persistence of immigrant and refugee newcomer students. It investigates whether newcomer adolescents’ academic persistence varies by the perceived supportiveness of school environments. Based on data collected from newcomer students in a medium-sized city in Canada, results show that immigrant and refugee youth display higher academic persistence when they perceive that their teachers support them and when their fellow students are receptive to diversity. Specifically, newcomer youth’s educational success depends on a school environment that encourages diversity and inter-group relations and teachers who are supportive of students, encourage them, and believe in them. This study also shows that newcomer youth are more likely to academically persist in school when they perceive that their fellow schoolmates exhibit cultural humility or openness to diversity and thus are interested in knowing more about immigrants’ country of origin, respect them, and interact with them.